Methodological Approaches To The Formation Of Medical Culture And A Healthy Lifestyle - Akmaljon Tursunpulatov (Penerbit Jurnal Indonesia, 2024)
In this article, we will try to analyze specific methodological approaches and methods for improving the medical culture of internal affairs officers. An internal affairs officer plays an important role in ensuring security as a guarantor of social responsibility and moral standards. As we have seen in the previous chapters, their role is not limited to enforcing the law, but also includes protecting justice and ensuring stability, which is especially important in the formation of medical culture.